Syndrome of inappropriate antidiuretic hormone secretion in hospital inpatients: a descriptive study in a tertiary care centre in South India - Abdulla, Mansoor C.; Alungal, Jemshad; Salih, Mohammed (International Journal of Research in Medical Sciences, 2017)
Background: Hyponatremia is the most common electrolyte abnormality among the patients in medical wards as well as in the intensive care unit contributing to substantial morbidity and mortality. The most common cause of hyponatraemia in hospital inpatients is Syndrome of Inappropriate Anti Diuretic Hormone secretion (SIADH). This prospective observational study was designed to assess the clinical profile of SIADH. Aim: To assess the clinical profile of SIADH in medically ill patients. Methods: This was an observational study for 24 months conducted in a tertiary care hospital. Patients were assessed clinically to study the volume status, effects of hyponatremia on nervous system and find out various etiologies for SIADH. All patients underwent routine hemogram, blood biochemistry, serum electrolytes, thyroid function tests, morning serum cortisol estimation, plasma and urinary osmolality determination as well as urinary sodium estimation. Patients were diagnosed to have Syndrome of Inappropriate Antidiuretic Hormone secretion (SIADH) if they satisfied the Bartter and Schwartz criteria. Results: Among the eighty patients with euvolemic, hypoosmolal hyponatremia who were screened for SIADH, seven patients were excluded due to various reasons (hypothyroidism, Sheehan’s syndrome, Addison’s disease). The mean age of the patients was 64 ± 13 years. Among 73 patients included there were 33 (45.2%) male patients and 40 (54.8%) female patients. Severe hyponatremia (Na <110 meq/l) was detected in 33 patients (45%). Pulmonary causes were the most common cause of SIADH in this study seen in 25 (34.2%). The other causes were idiopathic in 20 (27.4%), neurological in 17 (23.3%), drug induced in 2 (2.7%), positive pressure ventilation in 5 (6.8%) and other infections in 4 (5.5%).The average rate of correction was 5 meq ± 1.5 in the first 24 hours. The overall mortality was found to be 7%. Conclusion: Hyponatremia due to SIADH is common among elderly patients with preponderance for female population. Majority of the patients in the present study were noticed to have an underlying respiratory cause as the etiology. Mortality in SIADH patients was related to the underlying cause rather than the severity of hyponatremia.